Neoadjuvant therapy of prostate carcinoma: expectations and preliminary results - Siegsmund, Michael; Toktomambetova, Lira; Alken, Peter (Oncology research and treatment, 1999)
The goal of neoadjuvant androgen deprivation in prostate carcinoma is to reduce the volume of a locally advanced tumor by a short-term treatment, in order to improve the cure rate of the following radical prostatectomy or radiotherapy. In several studies, some of them randomized, it has been shown that the neoadjuvant therapy results in volume reduction of the prostate gland and in a sharp decline of the serum PSA levels. Furthermore, the percentage of positive surgical margins in clinical T2 tumors is significantly reduced, but there is no reduction of lymph node or seminal vesicle infiltration. Early results on biochemical progression do not show an advantage for neoadjuvant therapy before radical prostatectomy; however, 2 randomized studies demonstrate a significant improvement of local control and disease-specific survival with neoadjuvant androgen deprivation and external beam radiotherapy. Up to now, neoadjuvant androgen deprivation cannot be recommended generally with either radical prostatectomy or radiotherapy, although preliminary results of randomized trials, especially in conjunction with external beam radiation, are promising. Further studies especially need to deal with the optimal treatment period.